Synthesis and characterization of copolyarylates using tin octoate as a catalyst - Waghmare, P. B.; Pathak, P.; Deshmukh, S. A.; Idage, Susheela B.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A series of copolyarylates of bisphenol A (BPA) with varying ratios of diphenyl terephthalate (DPT) and diphenyl isophthalate (DPI) were prepared by melt polymerization at a temperature ranging from 200 to 290 degrees C under reduced pressure in the presence of tin octoate catalyst. Tin octoate catalyst has been extensively used for the preparation of biodegradable polymers namely, poly(lactic acid), poly(glycolic acid), and poly(lactide-glycolide) copolyesters. However, there are no reports on the preparation of copolyesters by melt polymerization using tin octoate catalyst. The effect of tin octoate catalyst was studied on the preparation of BPA/DPT/DPI copolyarylates. The copolyarylates were characterized by infrared and H-1 NMR spectroscopy, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The solution viscosities of copolyarylates were varied from 0.43 to 0.56 dL/g and the glass transition temperature (T-g) of copolyarylates was varied from 155 to 222 degrees C by varying the ratio of DPT and DPI. Most of the copolyarylates were found to be soluble in commonly used organic solvents and had film-forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: copolyarylates; diphenyl isophthalate; diphenyl terephthalate; melt polymerization; tin octoate